2008
DOI: 10.1029/2007jb005259
|View full text |Cite
|
Sign up to set email alerts
|

Eruption dynamics at Mount St. Helens imaged from broadband seismic waveforms: Interaction of the shallow magmatic and hydrothermal systems

Abstract: [1] The current eruption at Mount St. Helens is characterized by dome building and shallow, repetitive, long-period (LP) earthquakes. Waveform cross-correlation reveals remarkable similarity for a majority of the earthquakes over periods of several weeks. Stacked spectra of these events display multiple peaks between 0.5 and 2 Hz that are common to most stations. Lower-amplitude very-long-period (VLP) events commonly accompany the LP events. We model the source mechanisms of LP and VLP events in the 0.5-4 s an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
231
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(243 citation statements)
references
References 65 publications
12
231
0
Order By: Relevance
“…[71] We next investigate the possibility that the tilt was generated by a VLP source modeled by Waite et al [2008]. As noted earlier, VLP events during the summer of 2005 were found to be consistent with the opening and closing of a sill-dike combination located below the SW edge of the 1980s lava dome.…”
Section: Opening/closing Crack and Vlp Sourcementioning
confidence: 98%
See 3 more Smart Citations
“…[71] We next investigate the possibility that the tilt was generated by a VLP source modeled by Waite et al [2008]. As noted earlier, VLP events during the summer of 2005 were found to be consistent with the opening and closing of a sill-dike combination located below the SW edge of the 1980s lava dome.…”
Section: Opening/closing Crack and Vlp Sourcementioning
confidence: 98%
“…Iverson et al [2006] modeled the drumbeat events as caused by repeating slip on the margin of the ascending magma plug. Waite et al [2008] however, analyzed long-period seismic events recorded during the summer of 2005, and concluded that these events were inconsistent with a shear-faulting source and suggested instead the repetitive opening and closing of a steam-or fluid-filled crack or cracks located beneath the growing lava dome. Waite et al [2008] also analyzed very long period (VLP) events (periods of 15-25 s) during the same time and suggested that the source mechanism for these events involved the contraction and expansion of a sill and dike system located beneath the SW edge of the 1980s lava dome.…”
Section: The 2004-2008 Eruption Of Mount St Helensmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous source models exist to explain LP signals at volcanoes. These often invoke pressure fluctuations that result from the unsteady movement of bubbly magma [e.g., Chouet, 1996;Kumagai et al, 2002] or steam [Waite et al, 2008] through volcanic conduits and sometimes extend to include the venting of pressurized fluids into the atmosphere and generation of infrasound [Matoza et al, 2009]. Periodic strain changes induced by the oceanic microseism have also been cited as a trigger for hydrothermal LP events [Stich et al, 2011].…”
Section: Introductionmentioning
confidence: 99%